The Association between the Plasma Sugar and Lipid Profile with the Gene Expression of the Regulatory Protein of mTOR (Raptor) in Patients with Rheumatoid Arthritis. (18th August 2021) - Samimi, Zahra; Izadpanah, Arman; Feizollahi, Parisa; Roghani, Seyed Askar; Assar, Shirin; Zafari, Parisa; Taghadosi, Mahdi
ABSTRACT: Background: Rheumatoid arthritis (RA) is an autoinflammatory and self-perpetuating disease with both articular and extra-articular manifestations, such as cardiovascular complications, which are the leading cause of mortality and morbidity in RA patients. Impaired sugar and lipid metabolism are considered as the critical risk factors for cardiovascular disease (CVD). Regarding the regulatory function of Raptor in the immunometabolism, in this study, we evaluated the association between plasma sugar and lipid profiles with the gene expression of Raptor and the cytokine tumor necrosis factor-α (TNF-α), as an inflammatory mediator, in peripheral blood leukocyte of RA patients. Material and methods: Thirty-five RA patients who received combinational disease modified anti-rheumatoid drugs (DMARD) regimen and thirty healthy subjects enrolled in this study. The gene expression of Raptor was assessed by the real-time PCR method, and the Plasma levels of glucose and lipids, as well as TNF-α, were obtained using Hitachi device and enzyme-linked immunosorbent assay (ELISA) technique, respectively. Results: The gene expression of Raptor was reduced significantly in RA patients compared to the healthy subjects ( p = .001). The plasma level of HDL was significantly higher in RA patients than the control group ( p = .001), while the plasma level of LDL was reduced significantly in these patients ( p = .001). Conclusion: In our study, the reduced gene expression of Raptor may contribute to the impaired immunometabolism in RA patients, which is independent of plasma sugar and lipid profile.